Involucramiento político, un alcance conceptual desde la perspectiva de Bruce Pinkleton - Valdivieso Añazco, Isabel (2023)
The objective of the research was to identify the foundations of the concept of political involvement according to Bruce Pinkleton. He worked on the term political involvement in fifteen (15) academic articles within the field of study of political communication. The qualitative study of phenomenological design had as unit of analysis Professor Bruce Pinkleton and the choice of (07) seven articles of his scientific production as author and co-author, as an instrument of information collection a semi-structured interview guide and a registration form were applied and for data processing an analysis matrix was applied. As a result, it was found that the term political involvement is conceptualized as the interest of a citizen in politics and the search for sources and information in traditional media such as TV, radio, newspapers and social networks that favor decision making and political participation.